2020
DOI: 10.1039/d0tc03216f
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effect of fluorinated ligands in hybrid EUV photoresists by X-ray spectroscopy

Abstract: A fluorinated ligand in an extreme ultraviolet hybrid photoresist yields C–F bond dissociation upon exposure, thus enhancing its overall sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 56 publications
2
25
0
3
Order By: Relevance
“…Based on these results, the Zr oxo cluster film possesses significantly greater sensitivity than the Zr6O4 cluster film. We note that the sensitivity of the Zr6O4 cluster agrees with previous reports [3b,4d] . Meanwhile, the sensitivity of the Zr oxo cluster is equally good or even better, compared to other reported photoresists [3b,4d,23b] …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Based on these results, the Zr oxo cluster film possesses significantly greater sensitivity than the Zr6O4 cluster film. We note that the sensitivity of the Zr6O4 cluster agrees with previous reports [3b,4d] . Meanwhile, the sensitivity of the Zr oxo cluster is equally good or even better, compared to other reported photoresists [3b,4d,23b] …”
Section: Resultssupporting
confidence: 91%
“…As photoresists, the films of Zr6O4 clusters can be patterned in the presence or absence of photoacid generators (PAG) at EUV dose ranging from 50 to 100 mJ/cm 2 . Indeed, the sensitivity of the Zr6O4 film is considerably lower than that of ZrO 2 nanoparticles [4d,12a,15] . To obtain higher resolution, it is necessary to transcend the trade‐off relationship among resolution, line‐width‐roughness, and sensitivity [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that introduction of a – CF 3 group at the α position decreases the rate of radical homopolymerization of the TFMA unit. , Different molecular packing of the oxoclusters in Zn­(TFMA) compared to its analogue Zn­(MA)­(TFA) or a reduced ratio of the solubility rates of the unexposed and exposed regions in the developer of choice can also contribute toward this observed decrease in the sensitivity. Therefore, incorporation of more fluorine does not always directly translate into better EUVL performance of the photoresist, in contrast to the previous reported studies. , Further, contrast curve studies demonstrated that postexposure bake (PEB) applied at 120 °C/30 s under ambient conditions led to a further slight decrease in the sensitivity (also see section ). Spectroscopic studies to identify the chemical changes induced by PEB in the oxocluster were also carried out, and are discussed in section .…”
Section: Resultsmentioning
confidence: 65%
“…Therefore, incorporation of more fluorine does not always directly translate into better EUVL performance of the photoresist, in contrast to the previous reported studies. 23,40 Further, contrast curve studies demonstrated that postexposure bake (PEB) applied at 120 °C/30 s under ambient conditions led to a further slight decrease in the sensitivity (also see section 3.4). Spectroscopic studies to identify the chemical changes induced by PEB in the oxocluster were also carried out, and are discussed in section 3.7.…”
Section: Thin Films and Euv Contrast Curvesmentioning
confidence: 93%
“…The reaction scheme is similar to an earlier published reaction scheme. 62 When excited by 266 nm DUV pulses, the streak trace differs significantly from CB alone, as it is both red-shifted and decays on a longer time-scale. Fig.…”
Section: Xuv Excited Optical Luminescence a Xeol Behavior Of Sodium S...mentioning
confidence: 99%